THE INFLUENCE OF GENETICALLY MODIFIED PRODUCTS ON INTERNAL ORGANS - Khasanova Dilnoza Akhrorovna (Journal Park Publishing, 2024)
This article investigates the influence of genetically modified (GM) products on internal organs, aiming to elucidate the potential health implications of GM consumption. Through a comprehensive review of existing literature and research findings, the article examines the impact of GM foods on various internal organs, including the liver, kidneys, gastrointestinal tract, and reproductive organs. It explores mechanisms by which GM ingredients may interact with physiological processes, such as gene expression, immune response, and metabolic pathways. Additionally, the article discusses controversies and debates surrounding the safety of GM products, including allergenicity, toxicity, and long-term health effects. Insights from animal studies, human trials, and epidemiological research are synthesized to provide a holistic understanding of the relationship between GM consumption and internal organ health. By critically evaluating the evidence, this article contributes to informed discussions and decision-making regarding the regulation, labeling, and consumption of GM products.
Keywords: Genetically modified products, GM foods, internal organs, health implications, liver, kidneys, gastrointestinal tract, reproductive organs, gene expression, immune response, metabolic pathways, safety, allergenicity, toxicity, regulation, labeling.